Legal Regime of Inventions Created by Artificial Intelligence (Law, State and Telecommunications Review, 2024)
[Purpose] The purpose of this study is to examine the concept of artificial intelligence (AI) as an object of civil legal relations, with a specific focus on its status as an inventor. The study aims to define the characteristics of AI as an inventor, including its intangible nature, resemblance to the human brain, autonomy, data collection and processing capabilities, learning ability, and generation of novel results, particularly in the realm of inventions.[Methodology/Approach/Design] The research employs a range of methodologies, including functional and logical analysis, deduction, induction, synthesis, and dogmatic approaches. It highlights the need for legal regulation concerning AI as an inventor, with particular attention given to the legal regime surrounding inventions created by AI.[Findings] Based on the unique aspects of AI as an object of civil legal relations and its capacity to create inventions, the study proposes extending the existing legal and patent framework to address these relations with certain specificities. The conditions for patentability of AI-generated inventions should mirror those for human inventions, as they operate in the same technological field.[Practical Implications] It is not recommended to grant AI the status of a legal entity. Instead, the study suggests indicating in the patent that the invention was created with the assistance of a specific AI, without conferring personal non-property rights to AI itself. Property rights to inventions generated by AI should be legally assigned to the user of the AI, unless agreed upon differently by the parties involved.[Originality/Value] Given the advancements in AI technologies and their ability to create patentable inventions, there is an urgent need for comprehensive and effective legal regulation. Currently, such regulation is lacking at both the national and international levels, underscoring the significance and value of this study.